Corrigendum to “Ecological risk evaluation of sediment metals in a tropical Euthrophic Bay, Guanabara Bay, Southeast Atlantic” (Marine Pollution Bulletin (2016) 109(1) (435–445) (S0025326X16303319) (10.1016/j.marpolbul.2016.05.030)) - Abreu, Ilene Matanó; Cordeiroa, Renato Campello; Soares-Gomes, Abílio; Abessa, Denis Moledo S. [UNESP]; Maranho, Luciane Alves [UNESP]; Santelli, Ricardo Erthal (Elsevier, 2016)
The authors would like to note that the corresponding author of this paper has been changed to the following: Abilio Soares Gomes. abiliosg@id.uff.br Departamento de Biologia Marina, Universidade Federal Fluminense, P.O. Box 100.644, Niterói, RJ, 24001-970, Brazil. The authors would like to apologise for any inconvenience caused.